Climate Smart Agriculture Options for Myanmar Small-Holder Farmers: Education and Training Posters for Villages - International Institute of Rural Reconstruction (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
A series of educational posters promoting various climate-smart agriculture options, such as: boundary planting of green leaf manure trees; integration of perennial fruit trees; legumes and cover cropping; homestead production; improving seeds quality through better management and storage; backyard native pig farming; backyard native chicken farming; small scale goat rearing; small scale aquaculture for diversification; and promoting gender equality in agriculture in the climate smart villages.